2023
DOI: 10.1111/ele.14333
|View full text |Cite
|
Sign up to set email alerts
|

Climate dependence of the macrofaunal effect on litter decomposition—A global meta‐regression analysis

Nevo Sagi,
Dror Hawlena

Abstract: Litter decomposition by microorganisms and animals is influenced by climate and has been found to be higher in warm and wet than in cold and dry biomes. We, however, hypothesized that the macrofaunal effect on decomposition should increase with temperature and aridity since larger animals are more tolerant to aridity than smaller organisms. This hypothesis was supported by our global analysis of macrofauna exclusion studies. Macrofauna increased litter mass loss on average by 40%, twofold higher than the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
2
2
0
Order By: Relevance
“…Our synthesis shows 31% of forest leaf litter decomposition, globally, is mediated by invertebrates. Our estimate is in line with the previous estimates of invertebrate effects on litter decomposition in terrestrial biomes (27%–40%) (García‐Palacios et al., 2013; Kampichler & Bruckner, 2009; Sagi & Hawlena, 2023; Xu et al., 2020), but lower than instreams (74%) (Yue et al., 2022). Based on the existing findings, for example, the pattern of macrofaunal‐mediated decomposition across terrestrial ecosystems reported by Sagi and Hawlena (2023).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our synthesis shows 31% of forest leaf litter decomposition, globally, is mediated by invertebrates. Our estimate is in line with the previous estimates of invertebrate effects on litter decomposition in terrestrial biomes (27%–40%) (García‐Palacios et al., 2013; Kampichler & Bruckner, 2009; Sagi & Hawlena, 2023; Xu et al., 2020), but lower than instreams (74%) (Yue et al., 2022). Based on the existing findings, for example, the pattern of macrofaunal‐mediated decomposition across terrestrial ecosystems reported by Sagi and Hawlena (2023).…”
Section: Discussionsupporting
confidence: 92%
“…Our estimate is in line with the previous estimates of invertebrate effects on litter decomposition in terrestrial biomes (27%–40%) (García‐Palacios et al., 2013; Kampichler & Bruckner, 2009; Sagi & Hawlena, 2023; Xu et al., 2020), but lower than instreams (74%) (Yue et al., 2022). Based on the existing findings, for example, the pattern of macrofaunal‐mediated decomposition across terrestrial ecosystems reported by Sagi and Hawlena (2023). We further quantified a regional variation that the invertebrate effect in tropical and subtropical forests (38% on average) is 1.4 times higher than in forests elsewhere (26% on average).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations